2013
DOI: 10.1177/030089161309900607
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of bcl-2 expression as a prognostic marker in early stage laryngeal cancer

Abstract: No correlation was observed between bcl-2 expression and local control or overall survival. Whereas hemoglobin level, age and existence of a recurrence had a prognostic impact on overall survival, patient age and smoking status influenced local control rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Previous studies have reported that BCL2 is involved in the pathogenesis of laryngeal cancer (10)(11)(12). In the present study, it was observed that transfection of M4e cells with lenti-miR-34c significantly inhibited cell viability and BCL-2 protein expression, and increased the percentage of cells undergoing apoptosis.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Previous studies have reported that BCL2 is involved in the pathogenesis of laryngeal cancer (10)(11)(12). In the present study, it was observed that transfection of M4e cells with lenti-miR-34c significantly inhibited cell viability and BCL-2 protein expression, and increased the percentage of cells undergoing apoptosis.…”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, miR-34a/c expression was observed to be downregulated in human laryngeal squamous cell carcinoma tissues, and upregulation of miR-34a/c in Hep-2 cells by transfection significantly decreased cell proliferation and migratory ability in vitro (2). It was previously reported that B cell lymphoma 2 (BCL2), a central genetic apoptotic regulator (9), which is crucial for cell apoptosis, migration and invasion (3), is involved in the pathogenesis of laryngeal cancer (10)(11)(12). In addition, research into other diseases has reported on the association between miR-34c and BCL2 (13)(14)(15); there is an inverse association between levels of miR-34c and expression of BCL2.…”
Section: Introductionmentioning
confidence: 99%
“…The bcl2 gen encodes for a mitochondrial protein which prevents apoptosis and prolongs cell survival, thus antagonizing the effects of the p53 protein [37,38]. This suggest the possibility that increased expression of bcl-2 in mammary tumors from smokers' women determine a worse prognosis by preventing apoptosis [39] or be accompanied by a better prognosis as have been shown in these malignant neoplasms [40].…”
Section: Discussionmentioning
confidence: 96%